Biogenic Amines: Physiology, Toxicity, and the Importance of Agmatine - Khémesse , Kital; Moumouny , Traoré; François, Delattre; Alphonse, Tine (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Agmatine (AGM) is a biogenic amine that is present in shrimp and can be used as an indicator of its freshness and quality. In this study, we developed a spectrofluorimetric method for the determination of AGM in shrimp using orthophthalaldehyde (OPA) as the derivatization agent. The stoichiometry of the OPA-AGM complex was determined to optimize analytical results, and the effects of agitation and temperature on the fluorescence spectra of the complex in alkaline medium (pH 13) were studied. The method showed excellent analytical performance with very low detection limits (DL) ranging from 0.36 to 2.52 ng/mL and a quantification limit (QL) of 1.62 to 8.40 ng/mL. The relative standard deviations (RSD) obtained ranged from 0.08 to 1.5%, demonstrating the excellent replicability of measurements. The accuracy of measurements was confirmed by the recovery rates found in shrimp extract, which ranged from 96.3% to 103.4%. Furthermore, interference effects on the determination of agmatine rate with biogenic amines and some metal ions commonly present in shrimp were studied. The method presented here is a sensitive, accurate, and reliable tool for the determination of AGM in shrimp, and it has the potential to be used for the quality control of shrimp products in the food industry.